Stretching the Improvement of the Home Industry for Usek Paninggaran Crackers in the Islamic Economy - Refanza Riskiyani; Hendri Hermawan A (AL-MASHARIF: JURNAL ILMU EKONOMI DAN KEISLAMAN, 2021)
AbstractThe rise of the Home Industry business in Paninggaran District shows that the MSME sector is growing very rapidly. Paninggaran Village is one of the villages where community income is obtained from the sale of usek crackers. So it's not surprising that Paninggaran village is  known for its typical usek crackers. Usek crackers are known as sand crackers because during the frying process they use heated sand. The purpose of this study is to find out from an Islamic economic perspective about production management and marketing to branding of usek crackers at home in order to increase the economic value in Paninggaran Village. This study uses a type of field research (field research) and data collection methods using observation, interviews and documentation. The results of the research in the field show that the management of usek cracker production in Paninggaran Village is in line with Islamic law, although there is no labeling permit or brand marked as halal. This business is able to provide an increase in the economy of the cracker entrepreneur family and can reduce the unemployment rate for the community in Paninggaran Village.